Rezolvati ecuatia:
a) 3x - 4 = -1
b) 2(x - 1) = 3(x + 2)
c) (x - 1) (x + 2) = ( x - 2) (x - 1)
d) 3 - (x - 1) = (x + 2 ) x 4
e) x la adoua = 4
f) x la adoua - 9 = 0
Răspunsuri la întrebare
Răspuns de
0
a) 3x= -1+4
3x= 3 => x= 1
b) 2x-2=3x+6
2x-3x=6+2
-x=8=> x=-8
c)x²+2x-x-2=x²-x-2x+2
x² si -x se reduc=> 4x=4 => x=1
d) 3-x+1= 4x+8
-x-4x= 8-3-1
-5x= 5 => x= -1
e) x²=4 => x=2 deoarece 2²=4
f)x²-9=0 => x=3 deoarece 3²=9 iar 9-9 = 0 :)
3x= 3 => x= 1
b) 2x-2=3x+6
2x-3x=6+2
-x=8=> x=-8
c)x²+2x-x-2=x²-x-2x+2
x² si -x se reduc=> 4x=4 => x=1
d) 3-x+1= 4x+8
-x-4x= 8-3-1
-5x= 5 => x= -1
e) x²=4 => x=2 deoarece 2²=4
f)x²-9=0 => x=3 deoarece 3²=9 iar 9-9 = 0 :)
deniigbr:
ai înțeles ?
Alte întrebări interesante
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Istorie,
10 ani în urmă
Limba română,
10 ani în urmă
Limba română,
10 ani în urmă